A novel crystalline nanoporous iron phosphonate based metal–organic framework as an efficient anode material for lithium ion batteries. (5th August 2021) - Chakraborty, Debabrata; Dam, Tapabrata; Modak, Arindam; Pant, Kamal K.; Chandra, Bijan Krishna; Majee, Adinath; Ghosh, Aswini; Bhaumik, Asim
Abstract : A new Fe-MOF prepared by using a tetraphosphonic acid as a ligand is reported and it showed high specific capacity and excellent recycling efficiency in lithium-ion batteries. Abstract : Metal–organic framework (MOF) materials show extraordinary performances in several frontier applications of energy research due to their well-defined crystalline porous architecture, high specific surface area and the periodicity of the functional groups in their structures. Here, we report a new self-assembled nanoporous iron phosphonate material (H8 L-Fe-MOF) with a crystalline architecture. Hydrothermal synthesis was performed by using a novel (ethene-1, 1, 2, 2-tetrayltetrakis(benzene-4, 1-diyl))tetraphosphonic acid (TPE-acid, designated as H8 L) as the organic linker and the ferric (Fe 3+ ) ion precursor as a metal node. Several instrumental techniques were used for the characterization of this crystalline porous MOF. N2 adsorption–desorption analysis revealed the presence of a broad range of pores in nanoscale dimensions, together with a high BET surface area. The MOF crystal structure was resolved through Rietveld refinement from the powder XRD patterns using EXPO2014 and VESTA 3D. The computed unit cell parameters for this monoclinic phase are a = 28.211 Å, b = 12.265 Å, c = 10.533 Å, α = 90°, β = 99.295°, and γ = 90° together with a unit cell volume of 3597.33 Å 3 . FE-SEM image analysis revealed that tiny spherical nanocrystals with dimensions of ca. 3–4 nm self-assembled into H8 L-Fe-MOF. Elemental mapping and FT-IR spectroscopic data confirmed uniform distribution of iron over the organic tetraphosphonic acid ligand. TG-DTA suggested high thermal stability of H8 L-Fe-MOF. In lithium-ion batteries (LIBs), this organic–inorganic hybrid MOF can be used as an anode material. Here the counter cation plays a crucial role in stabilizing the material. Conceptually the robust nature and ordered crystalline framework of this MOF should open a new alternative to existing graphite-based anodes presently used in LIBs. Considering the progressive change in LIBs, which now incorporate solid electrolytes instead of organic carbonate-based liquid electrolytes, for improved safety in this present investigation we used a gel polymer electrolyte membrane to fabricate and characterize the device. This approach provides a better understanding of how the MOF will behave in an actual application. The device performs fairly well in terms of stability in the recycling process and shows a high specific capacity with excellent retention capacity.